2004
DOI: 10.1002/bit.20243
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of adherent human embryonic stem cells

Abstract: Standard human embryonic stem (HES) cell cryopreservation methodologies, including slow freezing and vitrification of colonies in suspension, are plagued by poor viability and high differentiation rates upon recovery. To facilitate research studies and clinical applications of HES cells, we have developed a cryopreservation technique based on stabilizing HES colonies adherent to or embedded in a Matrigel matrix. This method increases cell viability by over an order of magnitude compared with cryopreservation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 53 publications
6
129
0
Order By: Relevance
“…Finally, trehalose addition to the cryopreservation medium containing DMSO and fetal bovine serum (FBS) has been proven to increase the viability of hematopoietic precursor cells from 7% to 20% and improved membrane integrity in cryopreserved fetal skin cells (Erdag et al, 2002;Zhang et al, 2003). Ji et al showed that trehalose loading into adherent colonies of hESCs prior to cryopreservation results in small, but significant improvements in cell viability when combined with DMSO treatment and high FBS concentrations (Ji et al, 2004). In the same line of results, it has been demonstrated that trehalose addition to the freezing and post-thawing medium of hESC colonies cryopreserved in suspension in freezing medium containing 10% DMSO, increased the recovery rate by ~3 folds (from 15 to 48%) (Wu et al, 2005).…”
Section: Usage Of Different Cryoprotective Agents and Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, trehalose addition to the cryopreservation medium containing DMSO and fetal bovine serum (FBS) has been proven to increase the viability of hematopoietic precursor cells from 7% to 20% and improved membrane integrity in cryopreserved fetal skin cells (Erdag et al, 2002;Zhang et al, 2003). Ji et al showed that trehalose loading into adherent colonies of hESCs prior to cryopreservation results in small, but significant improvements in cell viability when combined with DMSO treatment and high FBS concentrations (Ji et al, 2004). In the same line of results, it has been demonstrated that trehalose addition to the freezing and post-thawing medium of hESC colonies cryopreserved in suspension in freezing medium containing 10% DMSO, increased the recovery rate by ~3 folds (from 15 to 48%) (Wu et al, 2005).…”
Section: Usage Of Different Cryoprotective Agents and Vehiclesmentioning
confidence: 99%
“…Similarly, hepatocytes sandwiched between two layers of collagen provide enhanced viability and protein secretion compared with cells preserved in solution (Birraux et al, 2002;Koebe et al, 1990;Koebe et al, 1999). Taking these results as a proof of principle, hESCs were successfully cryopreserved as adherent colonies in 24 well plates in medium containing 10% DMSO + 30% FBS by Ji et al (Ji et al, 2004). This approach demonstrated that hESCs frozen as adherent colonies were five times more viable than clumps of colonies frozen in suspension.…”
Section: Cryopreservation Of Adherent Versus Suspension Hpsc Coloniesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this difference in recovery may be due to differences in cell lines, freezing and thawing protocols, or growth substrate (49).…”
Section: Discussionmentioning
confidence: 99%
“…Trounson's group demonstrated that current methods of freezing, storage and recovery trigger apoptosis and spontaneous differentiation of hES with consequent loss of pluripotency Reubinoff et al 2000). Several other groups have also confirmed very low survival of hES cell after slow freezing with DMSO (Heng et al 2005;Ji et al 2004;Kim et al 2004).…”
Section: General Aspects Of Stem Cell Cryoconservation Conditions Cementioning
confidence: 99%